Aliskiren, a Direct Renin Inhibitor, Improves Vascular Endothelial Function in Patients on Hemodialysis Independent of Antihypertensive Effect ∼ a Pilot Study∼ - Hidekazu Moriya; Shuzo Kobayashi; Takayasu Ohtake; Daimu Tutumi; Yasuhiro Mochida; Kunihiro Ishioka; Machiko Oka; Kyoko Maesato; Sumi Hidaka; Shosaku Nomura (Karger Publishers, 2013)
Aims: Aliskiren inhibits the first step in the renin-angiotensin system (RAS) and recently has been shown to modulate vascular diseases via RAS-dependent and independent pathways. This study aimed to determine the effect of aliskiren-associated direct renin inhibition on endothelial function in patients on hemodialysis via flow-mediated dilatation (FMD) and platelet-derived microparticles (PDMP), as biomarkers of atherosclerosis. Methods: A 12-week prospective study was performed with 24 patients on hemodialysis who were administered 150 mg orally aliskiren once daily for 12 weeks. Results: No significant difference were observed between pre-dialysis, home, and weekly averaged blood pressure at baseline and at 12 weeks (151.5 ± 8.5/80.9 ± 12.9 mmHg vs 150.3 ± 15.3/78.9 ± 21.2 mmHg, 151.4 ± 9.7/82.3 ± 14.7 mmHg vs 151.2 ± 17.7/81.4 ± 10.6 mmHg, and 156.0 ± 18.3/81.9 ± 9.4 mmHg vs 152.5 ± 18.9/81.7 ± 12.3 mmHg, respectively). FMD significantly increased from 2.54% ± 1.45% at baseline to 3.11% ± 1.37% at 12 weeks (P = 0.0267), and PDMP significantly decreased from 13.9 ± 5.8 U/mL at baseline to 10.9 ± 4.5 U/mL at 12 weeks (P = 0.0002). Conclusion: Aliskiren improved vascular endothelial function and platelet-endothelium activation in patients on hemodialysis independent of antihypertensive effect.